Firms' Choice of Financiers in M&A Deals: The Value of Bank‐Firm Relationships. (4th July 2017) - Pantjes, Rik; Tümer‐Alkan, Günseli
Abstract : In this paper, we investigate the link between the financing of mergers and acquisitions deals and existing bank‐firm relationships by using a unique dataset consisting of forty M&A deals in the Netherlands from 2004 to 2012. The dataset allows us to identify the existing relationship lender to the firm and the offers received from different banks to finance the deal. The results indicate that the existing bank relationship is the most important factor for a firm when choosing the financier of the deal. As expected, loan price, fee and loan size determine the choice too. The existing relationship continues to be valuable during the crisis, however, other deal specific factors start to matter as well. Finally, when switching between banks firms make their decisions depending on the cost level, value of collateral and loan size. Overall, the results point to the value of bank‐firm relationships even though the borrowers may be relying too much on the old relationship bank.